2006
DOI: 10.3310/hta10220
|View full text |Cite
|
Sign up to set email alerts
|

Pressure relieving support surfaces: a randomised evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 51 publications
4
71
0
3
Order By: Relevance
“…Several factors have been proposed in the epidemiological literature as being associated with an increased risk of developing pressure ulcers at large; a consensus exists regarding impaired mobility, poor nutrition manifested by a low body mass index (BMI= bodyweight/squared-height [kg/m 2 ]) and loss of subcutaneous fat (Garcia and Thomas, 2006). However, clinical studies aimed at identifying risk factors specific for DTI are limited in sizes of patient groups and involvement of co-morbidities (Nixon et al, 2006). There is also little scientific evidence regarding risk factors specific for DTI (Stekelenburg et al, 2007;Elsner and Gefen, 2008;), though our group has previously suggested obesity as such (Elsner and Gefen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been proposed in the epidemiological literature as being associated with an increased risk of developing pressure ulcers at large; a consensus exists regarding impaired mobility, poor nutrition manifested by a low body mass index (BMI= bodyweight/squared-height [kg/m 2 ]) and loss of subcutaneous fat (Garcia and Thomas, 2006). However, clinical studies aimed at identifying risk factors specific for DTI are limited in sizes of patient groups and involvement of co-morbidities (Nixon et al, 2006). There is also little scientific evidence regarding risk factors specific for DTI (Stekelenburg et al, 2007;Elsner and Gefen, 2008;), though our group has previously suggested obesity as such (Elsner and Gefen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from the literature support this anecdotal evidence, one study found that 46% of alternating pressure mattresses were being used inappropriately; either having been installed incorrectly or were faulty [34]. A multi-centre randomised controlled trial (the PRESSURE trial [37]) identified numerous technical problems with both overlay and replacement systems, these are detailed in Table 1.…”
Section: Technological Advancesmentioning
confidence: 90%
“…During the trial we observed that grade 2 pressure ulcers did not usually receive dressings and other nursing care therefore we did not estimate for further treatment costs. 7 The health benefits associated with the interventions were captured as pressure ulcer free days. We chose this approach rather than the more usual method of trying to capture a patient's utility through changes in quality of life because concurrent illness would dominate any quality of life measurement.…”
Section: Discussionmentioning
confidence: 99%
“…7 Briefly, eligible people were aged at least 55 years who were admitted to vascular, orthopaedic, medical, or care of the elderly wards, either as acute or elective admissions, in the previous 24 hours. Inclusion criteria were an expected length of stay of at least seven days, and an expected (if elective) or actual limitation of activities and mobility or an existing pressure ulcer of grade 2, or both.…”
Section: Methodsmentioning
confidence: 99%